2011
DOI: 10.1089/lap.2011.0107
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Comparison Among Laparoscopic Duhamel, Laparotomic Duhamel, and Transanal Endorectal Pull-Through: A Single-Center, 18-Year Experience

Abstract: This study further supports technical advantages, lighter impact of the surgical procedure on infants, lower incidence of complications, and better long-term outcome of the transanal pull-through compared to the Duhamel approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 22 publications
1
29
0
8
Order By: Relevance
“…Most TEPTs were done as single-stage procedures, while staged procedures with preoperative colostomy were common in infants who underwent Duhamel pull-through. Five studies [16][17][18][19]22 reported the length of aganglionic segments. Duhamel pull-through consisted of 26 short, 132 rectosigmoid, and 18 long segments, and TEPT was composed of 16 short, 113 rectosigmoid, and 12 long segments.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most TEPTs were done as single-stage procedures, while staged procedures with preoperative colostomy were common in infants who underwent Duhamel pull-through. Five studies [16][17][18][19]22 reported the length of aganglionic segments. Duhamel pull-through consisted of 26 short, 132 rectosigmoid, and 18 long segments, and TEPT was composed of 16 short, 113 rectosigmoid, and 12 long segments.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Six studies 16,[18][19][20][21][22] were given four to six stars corresponding to a moderate risk of bias, and only one study 17 was given eight stars corresponding to a low risk of bias. Methodological weaknesses common to all studies included inadequate selection of both operative groups as all seven articles [16][17][18][19][20][21][22] were retrospective cohort studies. Demographic features and follow-up descriptions varied between studies (►Table 1).…”
Section: Study Qualitymentioning
confidence: 99%
“…Meta-analyses directly comparing these techniques demonstrated a shorter operating time in laparoscopic procedures and trans-anal procedures[51,52]. Reported length of stay for open procedures range from 6.9 to 18.7 d, laparoscopic-assisted procedures from 3.6 to 10.4 d and trans-anal endorectal procedures from 2.6 to 9.8 d. Two studies comparing laparoscopic vs open procedures showed a significantly shorter average length of stay with laparoscopic procedures; 4 d following the laparoscopic endorectal pull-through, 7 d with the laparoscopic Duhamel pull-through and 10 d after an open Duhamel pull-through[46,53]. When compared to the transabdominal approach, both the laparoscopic-assisted pull-through and the trans-anal endorectal pull-through have been shown to have a shorter length of stay[51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Another study suggested lower constipation rates and better continence at 1-year follow-up for the laparoscopic-assisted endoanal pull-through over the Duhamel procedure[53]. …”
Section: Discussionmentioning
confidence: 99%
“…Yöntemin uygulanabilirliği, ameliyat süresi ve komplikasyonları açısından diğer yöntemlerle karşılaştı-rıldığı çok sayıda çalışma vardır (2)(3)(4)(5)(6) . Uzun segment Hh'lı hastalarda, serbestleştirmenin-ameliyatın temel ilkesine görece ters düşmekle birlikte-laparatomi/laparoskopi yardımıyla yapılabilmesi yöntemin daha geniş bir hasta grubunda kullanılmaya başlanmasına yol açmıştır (7)(8)(9)(10)(11) .…”
Section: Introductionunclassified